Muzyka a emocje dziecka w wieku przedszkolnym = Music and emotion by preschool aged children - Szymajda, Agnieszka (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article describes the experience of music classes for preschool children with emotional difficulties. The children took part in a year`s program of individual lessons, based on creative activities inspired by music and methods of creative music therapy, Orff`s multi-sensorial music therapy, methods of rhythm.
Keywords: muzykoterapia kreatywna; rytmika; muzykoterapia Orffa; dziecko w wieku przedszkolnym; emocje; creative music therapy; rhythms; music therapy of Orff; child of preschool age; emotions